Valuing the cost of improving Chilean primary vaccination: a cost minimization analysis of a hexavalent vaccine - Ignacio Olivera; Carlos Grau; Hugo Dibarboure; Juan Pablo Torres; Gustavo Mieres; Luis Lazarov; Fabián P. Alvarez; Juan Guillermo López Yescas (BMC, 2020)
Abstract Background The phased withdrawal of oral polio vaccine (OPV) and the introduction of inactivated poliovirus vaccine (IPV) is central to the polio 'end-game' strategy. Methods We analyzed the cost implications in Chile of a switch from the vaccination scheme consisting of a pentavalent vaccine with whole-cell pertussis component (wP) plus IPV/OPV vaccines to a scheme with a hexavalent vaccine with acellular pertussis component (aP) and IPV (Hexaxim®) from a societal perspective. Cost data were collected from a variety of sources including national estimates and previous vaccine studies. All costs were expressed in 2017 prices (US$ 1.00 = $Ch 666.26). Results The overall costs associated with the vaccination scheme (4 doses of pentavalent vaccine plus 1 dose IPV and 3 doses OPV) from a societal perspective was estimated to be US$ 12.70 million, of which US$ 8.84 million were associated with the management of adverse events related to wP. In comparison, the cost associated with the 4-dose scheme with a hexavalent vaccine (based upon the PAHO reference price) was US$ 19.76 million. The cost of switching to the hexavalent vaccine would be an additional US$ 6.45 million. Overall, depending on the scenario, the costs of switching to the hexavalent scheme would range from an additional US$ 2.62 million to US$ 6.45 million compared with the current vaccination scheme. Conclusions The switch to the hexavalent vaccine schedule in Chile would lead to additional acquisition costs, which would be partially offset by improved logistics, and a reduction in adverse events associated with the current vaccines.